Handbook of research on developing engaging online courses - Thornburg, Amy W., 1973-; Abernathy, Dixie F., 1964-; Ceglie, Rob J., 1972- (Information Science Reference, 2020)
"This book explores topics related to the online learner, online course content, and effective online instruction"- Resumé vydavatel
Keywords: virtuální vzdělávání; e-learning; výukový software; virtual education; educational software; sborníky; papers of several authors